HEALTH INSURANCE CHARACTERISTICS ANALYSIS FOR VARIOUS RISK PROFILE - , Ridwan Herdiawan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
client The research aims to analyze the risk profile and learn more deeply about the health insurance product of the ten best insurance companies in Indonesia. From the results of the analysis of the product will be adjusted to the client risk profile so that it will be a recommendation for the client in choosing the best health insurance according to their risk profile. ology The method in this research is a literature study because this research is a type of qualitative research and the data is also obtained from the websites of the company or from the company itself. The researcher has not found similar studies in the past, so there is no benchmark for this research. In this research, the researcher used a scoring system to determine the risk of health insurance products. This scoring system is based on two characteristics of the product, the first is how much product warranty coverage and the second is how much coverage these products. Researchers also used the three possibilities in this scoring method, with 40% vs. 60%, 50% vs 50%, 60% vs. 40%. The results of this scoring system are grouped into three risk profiles, High, Medium and Low. For High Risk researchers determined range one to five, while for Medium Risk range five to nine, and for Low range nine to eighteen. suitability table between the risk The result of the research is in the form of a profiles and insurance products. There are twenty health insurance products, nine of them are products with a high risk profile, there are five products that have a medium risk profile and six of them have Low risk profile. research can Hopefully the results of this help clients in choosing the best health insurance products for them according to their own risk profiles, so that the benefits of these products can be enjoyed to the fullest.